The Effectiveness of Using Frozen Film to Improve Students’ Vocabulary in Second Grade at SMP Negeri 2 Nirunmas - Batkunda, Margareta; Piter Titirloloby; Olivir Srue (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
This research aims to determine the application of film media to increase the vocabulary of students at SMP Negeri 2 Nirunmas with the film Frozen in learning. The type of research used in this research is a qualitative method in the form of classroom action research. In this research, it was carried out in two cycle to increase students' vocabulary through film media. Implementation of classroom action research in each cycle consists of the stages of planning, implementation, observation, reflection. The sample in this research was eighth grade students at SMP Negeri 2 Nirunmas, totaling 30 students. The research instruments used in this research were observation, tests and interview sheets. The results of this research show that in the first cycle, namely carrying out tests, students obtained a percentage score of 62% of the number of students who received the less active category in increasing vocabulary. But classically in the first cycle, students achieved 75% in the very active category. The second cycle showed satisfactory results where students obtained a percentage score of 88% of the total number of students studied obtained the very active category, meaning that students at the stage of increasing their vocabulary achieved KKM ≥ 75. Based on the research results obtained, it can be concluded that by applying film media it can improve Vocabulary of students at SMP Negeri 2 Nirunmas.